Effects of Bacillus velezensis zk1 on the physiology and metabolism of peaches. (21st October 2021) - Zeng, Yaoying; Yu, Qian; Cheng, Shujun
Summary: Bacillus velezensis zk1 is the dominant bacterium that causing rot in peaches. However, the mechanisms through that this bacterium causes rot have not been elucidated. Here, we explored the mechanisms of peach decay caused by B . velezensis zk1. The invasion of B. velezensis zk1 in peaches resulted in an increase in glucose and arabinose contents in fruit tissues. Moreover, the relative conductivity of the fruit reached 84% after 4 days of culture with bacterial invasion. With the destruction of cells, the malondialdehyde content increased, whereas the vitamin C, dialdehyde, flavonoid and total phenol contents decreased. Polyphenol oxidase, superoxide dismutase, catalase, peroxidase, ascorbate peroxidase and ammonia lyase activities also decreased. Overall, these findings demonstrated that B . velezensis zk1 infection damaged peach chloroplasts, mitochondria, respiratory chain activity and related free radical scavenging enzyme systems, thereby disrupting the normal physiological metabolism of peaches and causing rot. Abstract : B. velezensis zk1 infection damaged peach chloroplasts, mitochondria, respiratory chain activity and related free radical scavenging enzyme systems, thereby disrupting the normal physiological metabolism of peaches and causing rot.